PENCARIAN BUDAYA MENGGUNAKAN ONTOLOGI DAN ATURAN BERBASIS SEMANTIC WEB UNTUK SISWA SD - Rendra Husni Thamrin (MULTITEK INDONESIA, 2016)
Internet users every year have increased rapidly. One function of the Internet is that it is used as a source of information. Keywords used in search engine will help to find information. Semantic Web technologies can be used to help make the search more effective system either globally or specifically. Certain material in this study could use material about Indonesian art and culture taught in social studies class IV Elementary School in the odd semester.  Ontology bridges the differences in perception between humans with a machine that generally break the words then looking into the query. In addition SWRL (Semantic Web Rule Language) is used by Ontology which has already made.